Increasing customer equity through customer relationships on social media - Febrian, Angga; Roslina, R; Wibasuri, Anggalia; Yopita, Y (Diponegoro International Journal of Business, 2024)
This paper aims to propose and test a model of the influence of customer relationships on increasing customer equity, which has implications for consumer purchase intentions of retail products influenced by social media. We sent an online questionnaire to 476 respondents. Data analysis used the AMOS 24 structural equation modeling approach with the stages of measurement models and structural models of hypothesis testing. The study's results explain that the three factors forming a customer relationship can affect an increase in customer equity. Of the three dimensions, only brand equity can increase consumer purchase intentions. Meanwhile, value equity and relationship equity have negative results on purchase intention. Online sales through social media not only focus on the products offered but also require building brand equity, which determines consumer purchase intentions.